The effects of corruption in entrepreneurial ecosystems on entrepreneurial intentions - Francesco Ceresia; Claudio Mendola (Administrative Sciences, 2019)
Although researchers have identified corruption as a factor capable of affecting the entrepreneurial ecosystem at the national level of analysis, scholars have reported conflicting results regarding the exact nature of the relationship between corruption and entrepreneurial intentions. This paper formulates some propositions about the complex relationship between corruption and entrepreneurship at different levels of analysis and it suggests and explores the socio-cultural consequences of such domains' interactions. Finally, the slippery-slope effect will be discussed as an intra-individual psychological mechanism that could explain why even morally-engaged people might replicate corrupt behaviors. The limitations of this work, and its implications for future researchers and for government policies will be analyzed..
Keywords: 350; corruption; perceived corruption; entrepreneurial intention; entrepreneurial ecosystem; entrepreneurial development